Aluminum alloy bar and its preparation method and application

By optimizing the composition ratio and heat treatment process of aluminum alloy rods, the problem that aluminum alloy materials in the prior art cannot take into account both high conductivity and high yield strength, and the significant improvement in yield strength and conductivity is achieved. It is suitable for conductor materials high performance requirements.

CN118979180BActive Publication Date: 2024-12-24CHINALCO MATERIALS APPL RES INST CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411448754.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-24
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Existing aluminum alloy materials cannot take into account both high conductivity and high yield strength, and cannot meet the needs of conductor aluminum alloys in the field of conductivity.

Method used

By optimizing the composition ratio of aluminum alloy rods, Cu, Ce, Er and B elements were added, and three-stage hot extrusion and two-stage aging heat treatment process were adopted, combined with cold drawing treatment, the ratio of Mg and Si was adjusted to Improve yield strength and conductivity.

Benefits of technology

The yield strength of aluminum alloy rods has been achieved to reach more than 300MPa and conductivity to reach more than 50% IACS, meeting the material application needs in the fields of radar, electromagnetic rail or transportation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an aluminum alloy bar and a preparation method and application thereof, belonging to the technical field of alloy materials. The aluminum alloy bar of the invention comprises the following components in weight percentage: Mg 0.6%~1.0%, Si 0.5%~0.9%, Cu 0.1%~0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.01%~0.04%, B 0.01%~0.02%, Ce 0.01%~0.04%; single impurity ≤0.05%, total impurity ≤0.15%, the remainder is Al, totaling 100%. The yield strength of the aluminum alloy bar of the invention reaches more than 300 MPa, and the electrical conductivity reaches more than 50% IACS.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alloy materials, and in particular to an aluminum alloy bar and a preparation method and application thereof. Background Art

[0002] Aluminum alloys are widely used in the field of electrical conductivity due to their good electrical conductivity. In the fields of radar, electromagnetic rails, transportation, etc., aluminum alloy extrusions are required to have good electrical conductivity while meeting high strength, in order to meet the lightweight and high electrical conductivity requirements of increasingly stringent engineering. Currently used aluminum alloy materials such as 7075-T6 (strength of about 503MPa, electrical conductivity of about 37.5%IACS) and 6061-T6 (strength of about 276MPa, electrical conductivity of about 43.1%IACS) cannot meet the requirements of strength and electrical conductivity at the same time. Therefore, how to improve the mechanical properties of aluminum alloy materials while ensuring high electrical conductivity is one of the development directions of conductor aluminum alloys.

[0003] The prior art discloses a rare earth reinforced aluminum alloy and its preparation method, the composition of which is: Zn 7.2%-8.0%, Mg 1.6%-2.2%, Cu 1.6%-2.4%, Ce 0.05%-0.1%, Sc 0.06%-0.2%, Zr 0.03%-0.15%, and the balance is Al; and Fe ≤1.8%, Si ≤0.05%. The tensile strength of the aluminum alloy extrusion prepared by the alloy can reach 539MPa, and the yield strength can reach 473MPa, but the conductivity is only about 42.3%IACS, which cannot take into account both conductivity and strength.

[0004] The prior art also discloses a high-conductivity and high-strength aluminum alloy and a preparation method thereof, wherein the composition is: Si 0.4%-0.45%, Mg 0.5%-0.55%, B 0.03%-0.08%, Ti 0.007%-0.015%, Ce 0.1%-0.2%, Er 0.05%-0.2%, Fe 0.2%-0.3%, Mn 0.005%-0.015%, Cr 0.008%-0.02%, Zr 0.01%-0.02%, Cu 0.01%-0.04%, Zn 0.01%-0.05%, and the rest is aluminum and unavoidable impurities. The conductivity of the aluminum alloy extrusion material prepared therefrom is above 57% IACS, but the tensile strength is only 170 MPa, which also fails to take into account both conductivity and strength. Summary of the invention

[0005] The main purpose of the present invention is to provide an aluminum alloy bar and a preparation method and application thereof, so as to solve the problem in the prior art that the aluminum alloy bar cannot have both high electrical conductivity and high yield strength.

[0006] In order to achieve the above object, according to one aspect of the present invention, an aluminum alloy bar is provided, comprising the following components in weight percentage:

[0007] Mg 0.6%~1.0%, Si 0.5%~0.9%, Cu 0.1%~0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.01%~0.04%, B 0.01%~0.02%, Ce 0.01%~0.04%; single impurity ≤0.05%, total impurity ≤0.15%, the balance is Al, totaling 100%.

[0008] Further, the aluminum alloy bar comprises the following components in weight percentage:

[0009] Mg 0.8%~1.0%, Si 0.5%~0.8%, Cu 0.2%~0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.02%~0.04%, B 0.01%~0.02%, Ce 0.02%~0.04%; single impurity ≤0.05%, total impurity ≤0.15%, the balance is Al, totaling 100%.

[0010] Furthermore, the weight ratio of Mg to Si is: 1<Mg / Si≤2.

[0011] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned aluminum alloy bar, comprising the following steps:

[0012] Step S1: preparing the materials according to the proportion of each component in the aluminum alloy bar, and smelting to obtain an aluminum alloy ingot;

[0013] Step S2: performing homogenization heat treatment on the aluminum alloy ingot to obtain a homogenization heat treated ingot;

[0014] Wherein, the homogenization heat treatment includes the first stage homogenization heat treatment and the second stage homogenization heat treatment in sequence;

[0015] The conditions of the first stage homogenization heat treatment include: heat treatment temperature of 380℃~420℃, holding time of 4~10h;

[0016] Step S3: hot extruding the homogenized heat treated ingot to obtain an extruded rod;

[0017] Step S4: cold drawing the extruded rod to obtain a drawn rod;

[0018] Step S5: performing solution heat treatment on the drawn rod to obtain a solution heat treated rod;

[0019] Step S6: sequentially performing stretching straightening and aging heat treatment on the solution heat treated rod to obtain an aluminum alloy rod;

[0020] Wherein, the aging heat treatment includes the first aging heat treatment and the second aging heat treatment in sequence;

[0021] The conditions of the first aging heat treatment include: heating temperature of 125°C to 145°C and holding time of 10 to 20 hours;

[0022] The conditions of the second aging heat treatment include: a heating temperature of 165°C to 185°C and a holding time of 4 to 36 hours.

[0023] Furthermore, the conditions of the second stage homogenization heat treatment include: the heat treatment temperature is 550°C to 570°C, and the insulation time is 8 to 32 hours.

[0024] Furthermore, the cold drawing amount of the cold drawing is 8% to 20%.

[0025] Furthermore, the deformation of the tensile straightening is ≤2%.

[0026] Furthermore, the hot extrusion process includes: the heating temperature of the head of the homogenization heat treatment ingot is 510°C~530°C, the heating temperature of the middle part is 495°C~510°C, the heating temperature of the tail part is 480°C~495°C, and the total insulation time is 30min~1h.

[0027] Furthermore, the hot extrusion process also includes: the heating temperature of the hot extrusion mold is 420°C~440°C, the heating temperature of the extrusion barrel in the mold is 410°C~430°C, and the extrusion outlet temperature is 520~530°C.

[0028] Furthermore, the extrusion speed of the hot extrusion is 3-4 m / min, and the extrusion ratio is 20-30.

[0029] Furthermore, the conditions of the solution heat treatment include: the solution heating temperature is 540°C to 560°C, and the solution holding time is 40min to 70min.

[0030] Furthermore, the aluminum alloy rod after the solution heat treatment is water quenched to 15°C~35°C, and then stretched, straightened and aging heat treated.

[0031] According to a third aspect of the present invention, there is provided application of the above-mentioned aluminum alloy rod or the aluminum alloy rod obtained by the above-mentioned preparation method in radar, electromagnetic track or transportation.

[0032] By applying the technical solution of the present invention, an aluminum alloy bar and a preparation method thereof are provided. By optimizing the ratio of each component in the aluminum alloy raw material, each element synergistically exerts a greater high yield strength and high conductivity effect; by adding Cu element and a small amount of Ce, Er and B elements, the mechanical strength and electrical conductivity of the aluminum alloy bar are further improved; by adopting three-stage extrusion conditions and a suitable extrusion ratio, the strength and electrical conductivity of the aluminum alloy bar are further improved; the yield strength of the aluminum alloy bar of the present invention reaches more than 300 MPa, and the electrical conductivity reaches more than 50% IACS. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The description, which constitutes a part of this application, is used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention. DETAILED DESCRIPTION

[0035] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0036] In view of the problem that the aluminum alloy bar in the prior art cannot have both high yield strength and high electrical conductivity, the present invention develops an aluminum alloy bar, the raw material formula of which includes the following components in weight percentage:

[0037] Mg 0.6%~1.0%, Si 0.5%~0.9%, Cu 0.1%~0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.01%~0.04%, B 0.01%~0.02%, Ce 0.01%~0.04%; single impurity ≤0.05%, total impurity ≤0.15%, the balance is Al, totaling 100%.

[0038] The weight proportion of Mg, a constituent element of the aluminum alloy bar of the present invention, is selected from any value among 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1.0%, or any range between two values; the weight proportion of Si is selected from any value among 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, or any range between two values; the weight proportion of Cu is selected from any value among 0.1%, 0.15%, 0.9%, 0.95%, 1.0%, or any range between two values; .2%, 0.25%, 0.3%, 0.35%, 0.4% or any range between two of them; the weight proportion of Er is selected from any value among 0.01%, 0.02%, 0.03%, 0.04% or any range between two of them; the weight proportion of B is selected from any value among 0.01%, 0.015%, 0.02% or any range between two of them; the weight proportion of Ce is selected from any value among 0.01%, 0.02%, 0.03%, 0.04% or any range between two of them.

[0039] The existing forms of Si and Mg elements in the matrix of the components of the present invention have a direct impact on the electrical conductivity and strength of the alloy; the Mg element combines with the Si element to form a Mg2Si phase, which can increase the yield strength of the alloy to a certain extent; at the same time, after adjusting the excess of Mg element and undergoing reasonable heat treatment, the Mg2Si particles can be fully precipitated, which is also beneficial to improving the electrical conductivity of the alloy.

[0040] The components of the present invention add Cu element and a small amount of Ce, Er and B elements; Cu element is beneficial to further improve the strength of the alloy, Ce and Er elements can form intermetallic compounds with Si, Fe and the like to produce strengthening and stabilizing effects, and also have the effects of solid solution strengthening and grain refinement, and take into account the requirement of high strength while ensuring good electrical conductivity; B element can form compounds with impurity elements such as Ti and V to purify the melt and further improve the electrical conductivity of the alloy.

[0041] The yield strength of the aluminum alloy extruded rod developed by the present invention reaches more than 300 MPa, and the electrical conductivity reaches more than 50% IACS, specifically 300-350 MPa, and the electrical conductivity reaches 50%-55% IACS.

[0042] As a more preferred embodiment, the aluminum alloy bar raw material of the present invention comprises the following components in weight percentage:

[0043] Mg 0.8%~1.0%, Si 0.5%~0.8%, Cu 0.2%~0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.02%~0.04%, B 0.01%~0.02%, Ce 0.02%~0.04%; single impurity ≤0.05%, total impurity ≤0.15%, the balance is Al, totaling 100%.

[0044] The present invention further regulates the ratio of Mg, Si, Cu, Er, B, Ce, etc. in the aluminum alloy bar so that the above-mentioned specific elements can play a better synergistic role, thereby further improving the yield strength and electrical conductivity of the aluminum alloy bar. The yield strength reaches above 310 MPa, and the electrical conductivity reaches above 51% IACS; specifically, it can reach 310-350 MPa, and the electrical conductivity reaches 51%-55% IACS.

[0045] As a more preferred embodiment, the aluminum alloy bar raw material of the present invention comprises the following components in weight percentage:

[0046] Mg 0.9%~1.0%, Si 0.5%~0.6%, Cu 0.25%~0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.025%~0.04%, B 0.015%~0.02%, Ce 0.025%~0.04%; single impurity ≤0.05%, total impurity ≤0.15%, the balance is Al, totaling 100%.

[0047] The present invention further regulates the ratio of Mg, Si, Cu, Er, B, Ce, etc. in the aluminum alloy bar so that the above specific elements can play a better synergistic role, thereby further improving the yield strength and electrical conductivity of the aluminum alloy bar. The yield strength reaches 315-350 MPa, and the electrical conductivity reaches above 51.5%-53% IACS.

[0048] As a preferred embodiment, the weight ratio of Mg and Si in the elemental composition of the aluminum alloy bar of the present invention is: 1<Mg / Si≤2; it can be further controlled to be 1.1≤Mg / Si≤2, 1.2≤Mg / Si≤2; specifically, Mg / Si is any value among 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or a range value between any two of them.

[0049] The present invention controls the ratio of the constituent elements Si and Mg to be greater than 1 and less than or equal to 2, and the Mg element is combined with the Si element to generate a Mg2Si phase, which can further increase the yield strength of the alloy; at the same time, after the Mg element is added in a specific ratio and subjected to reasonable heat treatment, the Mg2Si particles can be fully precipitated, which can further improve the electrical conductivity of the alloy.

[0050] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned aluminum alloy bar, comprising the following steps:

[0051] Step S1: preparing the materials according to the proportion of each component in the aluminum alloy bar, and smelting to obtain an aluminum alloy ingot;

[0052] Step S2: performing homogenization heat treatment on the aluminum alloy ingot to obtain a homogenization heat treated ingot;

[0053] The homogenization heat treatment process includes a first-stage homogenization heat treatment process and a second-stage homogenization heat treatment process in sequence; the first-stage homogenization heat treatment process includes: a heat treatment temperature of 380°C to 420°C and a heat preservation time of 4 to 10 hours;

[0054] Step S3: hot extruding the homogenized heat treated ingot to obtain an extruded rod;

[0055] Step S4: cold drawing the extruded rod to obtain a drawn rod;

[0056] Step S5: performing solution heat treatment on the drawn rod to obtain a solution heat treated rod;

[0057] Step S6: sequentially performing stretching straightening and aging heat treatment on the solution heat treated rod to obtain an aluminum alloy rod; wherein:

[0058] The aging heat treatment process includes a first aging heat treatment process and a second aging heat treatment process in sequence;

[0059] The heating temperature of the first aging heat treatment process is 125℃~145℃, and the holding time is 10~20h;

[0060] The heating temperature of the second aging heat treatment process is 165℃~185℃, and the holding time is 4~36h.

[0061] The first-stage homogenization heat treatment temperature of the homogenization heat treatment in step S2 of the present invention is selected from any value of 380°C, 390°C, 400°C, 410°C, 420°C, or a range between any two thereof; the insulation time is any value of 4h, 5h, 6h, 7h, 8h, 9h, 10h, or a range between any two thereof.

[0062] The present invention adopts a two-step homogenization heat treatment, especially specifically designs the first-stage heat treatment temperature and the holding time, which can better eliminate the effects of dendrite segregation and dissolution of the soluble second phase, and is beneficial to improving the strength and conductivity of the aluminum alloy.

[0063] The heating temperature of the first aging heat treatment process of the present invention is 125°C~145°C, and the holding time is 10~20h; specifically, any value among 125°C, 130°C, 135°C, 140°C, 145°C or a range value between any two of them can be selected; the time can be any value among 10 h, 13 h, 15 h, 18 h, 20 h or a range value between any two of them.

[0064] The heating temperature of the second aging heat treatment process of the present invention is 165°C~185°C, and the holding time is 4~36h; specifically, any value among 165, 170, 175, 180, 185 or a range value between any two of them can be selected; the time can be any value among 4 h, 5 h, 10 h, 15 h, 20 h, 25 h, 30 h, 36 h or a range value between any two of them.

[0065] The double-stage aging using the above-mentioned specific process conditions can effectively suppress the room temperature parking effect of the aluminum alloy extruded material, which is beneficial for the prepared aluminum alloy extruded bar to form a more stable microstructure and promote the strength and conductivity of the bar.

[0066] In the above process of the present invention, the homogenization heat treatment process and the aging heat treatment process have an important influence on the strength and electrical conductivity of the alloy; the use of the above process conditions can promote the strength and electrical conductivity of the aluminum alloy rod.

[0067] As a preferred embodiment, the second stage homogenization heat treatment process includes: the heat treatment temperature is 550°C to 570°C, and the insulation time is 8 to 32 hours.

[0068] The second stage heat treatment temperature of the present invention is selected from 550°C, 560°C, and 570°C, and the insulation time is selected from any value among 8h, 10h, 13h, 15h, 18h, 20h, 23h, 25h, 28h, 30h, and 32h, or a range value between any two of them.

[0069] The present invention adopts the above-mentioned specific second-stage homogenization heat treatment process conditions after the above-mentioned specific first-stage homogenization heat treatment, which can further improve the aluminum alloy extruded rod to form a more stable microstructure and further promote the strength and conductivity of the rod.

[0070] As a preferred embodiment, the cold drawing amount of cold drawing is 8%~20%; the deformation amount of stretching straightening is 0~2%; for example, the cold drawing amount of the present invention can be controlled at any value of 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any range between two values.

[0071] The present invention adopts a cold drawing process after the hot extrusion process and adopts the cold drawing amount within the above range to further improve the grain structure morphology of the aluminum alloy extruded rod, and the grains are fine, which is beneficial to promoting material strength and improving electrical conductivity.

[0072] As a preferred embodiment, the temperature of hot extrusion of the present invention is divided into three sections, and different heating temperatures and holding times are used for the head (or head section), middle (middle section) and tail (tail section) of the heat-treated ingot to carry out the hot extrusion process: the heating temperature of the head is 510°C~530°C, the heating temperature of the middle is 495°C~510°C, the heating temperature of the tail is 480°C~495°C, and the total holding time is 30min~1h.

[0073] The head portion of the present invention is a section of the ingot body that comes out of the extruder first, and its specific length is 1 / 5 to 2 / 5 of the length of the ingot body near the head end of the ingot; the tail portion is a section of the ingot body that comes out of the extruder later, and its specific length is 1 / 5 to 2 / 5 of the length of the ingot body near the tail end of the ingot; the middle portion is 1 / 5 to 2 / 5 of the ingot body between the head portion and the tail portion; preferably, the length of the head portion, the length of the middle portion and the length of the tail portion are all 1 / 3 of the total length of the ingot body.

[0074] The heating temperature of the hot extrusion head of the present invention can be selected from any value of 510°C, 515°C, 520°C, 525°C, 530°C or a range between any two of them; the heating temperature of the middle part can be selected from any value of 495°C, 500°C, 505°C, 510°C or a range between any two of them; the heating temperature of the tail part can be selected from any value of 480°C, 485°C, 490°C, 495°C or a range between any two of them.

[0075] The traditional hot extrusion process uses the same temperature, and the performance of the head end and the tail end of the aluminum alloy rod is quite different, which will affect the strength and conductivity of the material; the present invention designs different heating temperatures for the head, middle and tail parts according to the different sequences of extrusion of the rods, which can ensure the uniformity of the quality and mechanics of the extruded material, and can ensure that the rod material has good yield strength and conductivity.

[0076] As a preferred embodiment, the hot extrusion process also includes: the heating temperature of the hot extrusion die is 420°C~440°C (for example, 420°C), the heating temperature of the extrusion barrel in the die is 410°C~430°C (for example, 430°C), the extrusion outlet temperature is ≥520°C, for example, 520°C, 525°C, 530°C; the extrusion speed is 3~4m / min, and the extrusion ratio is ≥20, for example, 20~30, specifically 20, 22, 25, 28, 30. The heating temperature of the hot extrusion die of the present invention can be selected from 420°C, 430°C, and 440°C; the heating temperature of the extrusion barrel can be selected from 410°C, 420°C, and 430°C.

[0077] The present invention adopts a higher outlet temperature of ≥520°C and a larger extrusion ratio of ≥20 during the hot extrusion process; on the one hand, this is to reduce the negative impact of dislocations and subgrains on electrical conductivity during the extrusion process, and on the other hand, it is beneficial to improve the strength of the alloy.

[0078] The heating temperature of the hot extrusion die of the present invention is the same as or similar to the temperature of the extrusion barrel. The temperature can be adjusted according to the characteristics of the aluminum alloy components. If it is too low, the hot extrusion effect cannot be achieved, and if it is too high, the extrusion quality will be affected.

[0079] As a preferred embodiment, the process of the solution heat treatment of the present invention includes: the solution heating temperature is 540°C to 560°C, the solution holding time is 40min to 70min, and water quenching is performed to room temperature (15°C to 35°C) after the solution. The solution heating temperature of the present invention can be selected from 540°C, 550°C, and 560°C; the solution holding time can be selected from 40 min, 50 min, 60 min, and 70 min.

[0080] The present invention adopts the above-mentioned solid solution heat treatment process conditions to make the strengthening phase fully dissolve back into the matrix to form a supersaturated solid solution, which is dispersed and precipitated during the aging process, thereby improving the strength of the alloy.

[0081] As a more specific embodiment, the processing method of the aluminum alloy bar of the present invention includes:

[0082] (1) The aluminum alloy ingot is heated from room temperature to 380°C~420°C and kept at this temperature for 4h~10h, and then heated to 550°C~570°C and kept at this temperature for 8h~32h to obtain an aluminum alloy extruded ingot after homogenization heat treatment.

[0083] (2) The extruded ingot after homogenization heat treatment is heated in sections, with the heating temperature of the head being 510℃~530℃, the heating temperature of the middle being 495℃~510℃, and the heating temperature of the tail being 480℃~495℃. The temperature is kept for 30min~1h, and then extrusion is carried out. The temperature of the extrusion barrel is 420℃, the temperature of the extrusion die is 430℃, the extrusion speed is 3-4m / min, the extrusion ratio is ≥20, and the extrusion outlet temperature is ≥520℃.

[0084] (3) The extruded material is cold drawn with a cold drawing amount of 8% to 20%.

[0085] (4) The extruded material after cold drawing is subjected to solution heat treatment. The solution treatment system is as follows: solution temperature 540℃~560℃, solution holding time 40min~70min, immersion water quenching to room temperature within 20s after solution treatment, and straightening or pre-deformation with a deformation of 0%~2% after solution treatment.

[0086] (5) The straightened or pre-deformed extruded material is subjected to aging heat treatment. The aging heat treatment process is as follows: the first-stage aging treatment temperature is 125°C~145°C, and the heat preservation is 10~20h; the second-stage aging treatment temperature is 165°C~185°C, and the heat preservation is 4~36h, and then cooled to room temperature. The cooling medium is air.

[0087] The invention improves the electrical conductivity of the alloy while ensuring the mechanical properties by designing the alloy elements and coordinating a reasonable heat treatment system and extrusion process.

[0088] The aluminum alloy bar provided by the present invention or the aluminum alloy bar obtained by the above preparation method has a yield strength of more than 300 MPa and an electrical conductivity of more than 50% IACS, which can meet the material application requirements in the fields of radar, electromagnetic rails or transportation.

[0089] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0090] In the preparation method of the embodiment of the present invention, a universal stretching machine is used to detect the yield strength of the aluminum alloy bar product; and an eddy current conductivity tester is used to detect the conductivity.

[0091] The lengths of the head, middle and tail of the ingot in the embodiments of the present invention and the comparative examples are the same as those in Example 1.

[0092] Example 1

[0093] An aluminum alloy extruded bar, wherein the proportions of its component elements are as follows: by weight percentage, Mg 1.0%, Si 0.5%, Cu 0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.04%, B 0.02%, Ce0.04%, single impurity ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0094] The weight ratio of Mg element and Si element is controlled to be Mg / Si at 2; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot.

[0095] The ingot was heated from room temperature to 420°C and kept at this temperature for 10 hours, and then heated to 570°C and kept at this temperature for 32 hours to obtain an extruded ingot after homogenization heat treatment.

[0096] The homogenized heat treated extruded ingot is extruded, and the extrusion process is as follows: the homogenized heat treated extruded ingot is heated in sections, the head (1 / 3 of the ingot length) is heated to 530°C, the middle (the middle 1 / 3 of the ingot length) is heated to 510°C, and the tail (1 / 3 of the ingot length) is heated to 495°C, and kept warm for 1 hour. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 4m / min, the extrusion ratio is 30, and the extrusion outlet temperature is 530°C.

[0097] After extrusion, the extruded material is cold drawn with a cold drawing amount of 20%. After cold drawing, it is subjected to solution heat treatment with a solution temperature of 560°C and a solution holding time of 70 minutes. After solution treatment, it is immediately immersed in water and cooled to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0098] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first stage aging temperature was 145°C, and the temperature was kept for 20 h; the second stage aging temperature was 185°C, and the temperature was kept for 36 h; and the extruded material was air-cooled to room temperature to obtain the corresponding aluminum alloy extruded material; the performance test results of the obtained aluminum alloy extruded bars are shown in Table 1.

[0099] Example 2

[0100] An aluminum alloy extruded bar material, wherein the proportions of its component elements are as follows: by weight percentage, Mg 0.9%, Si 0.6%, Cu 0.25%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.025%, B 0.015%, Ce0.025%, individual impurities ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0101] The weight ratio of Mg and Si is controlled to be 1.5; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot.

[0102] The desired ingot is obtained by casting.

[0103] The ingot was heated from room temperature to 400°C and kept at this temperature for 7 hours, and then heated to 560°C and kept at this temperature for 20 hours to obtain an extruded ingot after homogenization heat treatment.

[0104] The homogenized heat treated extruded billet is extruded, and the extrusion process is as follows: the homogenized heat treated extruded billet is heated in sections, the head is heated to 520°C, the middle is heated to 500°C, the tail is heated to 485°C, and the temperature is kept for 40 minutes. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 3.5m / min, the extrusion ratio is 25, and the extrusion outlet temperature is 520°C.

[0105] After extrusion, the extruded material is cold drawn with a cold drawing amount of 14%. After cold drawing, it is subjected to solid solution heat treatment with a solid solution heat treatment system of 550°C and a solid solution holding time of 55 minutes. After solid solution, it is immediately immersed in water cooling to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0106] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first stage aging temperature was 135°C, and the temperature was kept for 15 h; the second stage aging temperature was 175°C, and the temperature was kept for 20 h; and the extruded material was air cooled to room temperature to obtain the corresponding aluminum alloy extruded rods; the performance test results of the extruded rods obtained are shown in Table 1.

[0107] Example 3

[0108] An aluminum alloy extruded bar, wherein the proportions of its component elements are as follows: by weight percentage, Mg 0.6%, Si 0.5%, Cu 0.1%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.01%, B 0.01%, Ce0.01%, individual impurities ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0109] The weight ratio of Mg to Si is controlled to be 1.2. The raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio and cast to obtain the required ingot.

[0110] The ingot was heated from room temperature to 380°C and kept at this temperature for 4 hours, and then heated to 550°C and kept at this temperature for 8 hours to obtain an extruded ingot after homogenization heat treatment.

[0111] The homogenized heat treated extruded billet is extruded, and the extrusion process is as follows: the homogenized heat treated extruded billet is heated in sections, the head is heated to 510°C, the middle is heated to 495°C, the tail is heated to 480°C, and the temperature is kept for 0.5h. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 3m / min, the extrusion ratio is 20, and the extrusion outlet temperature is 510°C.

[0112] After extrusion, the extruded material is cold drawn with a cold drawing amount of 8%. After cold drawing, it is subjected to solution heat treatment with a solution temperature of 540°C and a solution holding time of 40 minutes. After solution, it is immediately immersed in water and cooled to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0113] The straightened extruded material was subjected to aging heat treatment. The aging heat treatment system was as follows: the first aging temperature was 125°C, and the temperature was kept for 10 hours. The second aging temperature was 165°C, and the temperature was kept for 4 hours. The extruded material was cooled to room temperature by air to obtain the corresponding aluminum alloy extruded material. The performance test results of the extruded material are shown in Table 1.

[0114] Example 4

[0115] An aluminum alloy extruded bar, wherein the proportions of its component elements are as follows: by weight percentage, Mg 0.8%, Si 0.7%, Cu 0.3%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.03%, B 0.02%, Ce0.03%, individual impurities ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0116] The weight ratio of Mg and Si is controlled to be 1.14; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot.

[0117] The ingot was heated from room temperature to 410°C and kept at this temperature for 8 hours, and then heated to 565°C and kept at this temperature for 25 hours to obtain an extruded ingot after homogenization heat treatment.

[0118] The homogenized heat treated extrusion billet is extruded, and the extrusion process is as follows: the homogenized heat treated extrusion billet is heated in sections, the head is heated to 525°C, the middle is heated to 505°C, the tail is heated to 490°C, and the temperature is kept for 50 minutes. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 3.5m / min, the extrusion ratio is 30, and the extrusion outlet temperature is 525°C.

[0119] After extrusion, the extruded material is cold drawn with a cold drawing amount of 16%. After cold drawing, it is subjected to solid solution heat treatment with a solid solution heat treatment system of 555°C and a solid solution holding time of 60 minutes. After solid solution, it is immediately immersed in water cooling to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0120] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first-level aging temperature was 140°C, and the temperature was kept for 18 hours; the second-level aging temperature was 180°C, and the temperature was kept for 25 hours; and the extruded material was air-cooled to room temperature to obtain the corresponding aluminum alloy extruded material; the performance test results of the obtained aluminum alloy extruded bars are shown in Table 1.

[0121] Example 5

[0122] An aluminum alloy extruded bar, wherein the proportions of its component elements are as follows: by weight percentage, Mg 1.0%, Si 0.8%, Cu 0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.04%, B 0.02%, Ce0.04%, individual impurities ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0123] The weight ratio of Mg and Si is controlled to be 1.25; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot.

[0124] The ingot was heated from room temperature to 385°C and kept at this temperature for 6 hours, and then heated to 555°C and kept at this temperature for 10 hours to obtain an extruded ingot after homogenization heat treatment.

[0125] The homogenized heat treated extruded billet is extruded, and the extrusion process is as follows: the homogenized heat treated extruded billet is heated in sections, the head is heated to 515°C, the middle is heated to 500°C, the tail is heated to 485°C, and the temperature is kept for 1 hour. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 4m / min, the extrusion ratio is 25, and the extrusion outlet temperature is 515°C.

[0126] After extrusion, the extruded material is cold drawn with a cold drawing amount of 10%. After cold drawing, it is subjected to solution heat treatment with a solution temperature of 545°C and a solution holding time of 50 minutes. After solution treatment, it is immediately immersed in water and cooled to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0127] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first stage aging temperature was 130°C, and the temperature was kept for 13 hours; the second stage aging temperature was 170°C, and the temperature was kept for 8 hours; and the extruded material was air-cooled to room temperature to obtain the corresponding aluminum alloy extruded material; the performance test results of the obtained aluminum alloy extruded bars are shown in Table 1.

[0128] Example 6

[0129] An aluminum alloy extruded bar, wherein the proportions of its component elements are as follows: by weight percentage, Mg 1.0%, Si 0.5%, Cu 0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.04%, B 0.02%, Ce0.04%, single impurity ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0130] The weight ratio of Mg element and Si element is controlled to be Mg / Si at 2; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot.

[0131] The ingot was heated from room temperature to 420°C, kept at this temperature for 10 hours, and then raised to 500°C, kept at this temperature for 6 hours to obtain an extruded ingot after homogenization heat treatment.

[0132] The homogenized heat treated extrusion billet is extruded, and the extrusion process is as follows: the homogenized heat treated extrusion billet is heated in sections, the head is heated to 530°C, the middle is heated to 510°C, the tail is heated to 495°C, and the temperature is kept for 1 hour. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 4m / min, the extrusion ratio is 30, and the extrusion outlet temperature is 530°C.

[0133] After extrusion, the extruded material is cold drawn with a cold drawing amount of 20%. After cold drawing, it is subjected to solution heat treatment with a solution temperature of 560°C and a solution holding time of 70 minutes. After solution treatment, it is immediately immersed in water and cooled to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0134] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first stage aging temperature was 145°C, and the temperature was kept for 20 h; the second stage aging temperature was 185°C, and the temperature was kept for 36 h; and the extruded material was air-cooled to room temperature to obtain the corresponding aluminum alloy extruded material; the performance test results of the obtained aluminum alloy extruded bars are shown in Table 1.

[0135] Example 7

[0136] An aluminum alloy extruded bar, wherein the proportions of its component elements are as follows: by weight percentage, Mg 1.0%, Si 0.5%, Cu 0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.04%, B 0.02%, Ce0.04%, single impurity ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0137] The weight ratio of Mg element and Si element is controlled to be Mg / Si at 2; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot.

[0138] The ingot was heated from room temperature to 420°C and kept at this temperature for 10 hours, and then heated to 520°C and kept at this temperature for 6 hours to obtain an extruded ingot after homogenization heat treatment.

[0139] The homogenized heat treated extrusion billet is extruded, and the extrusion process is as follows: the homogenized heat treated extrusion billet is heated in sections, the head is heated to 530°C, the middle is heated to 510°C, the tail is heated to 495°C, and the temperature is kept for 1 hour. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 4m / min, the extrusion ratio is 30, and the extrusion outlet temperature is 530°C.

[0140] After extrusion, the extruded material is cold drawn with a cold drawing amount of 5%. After cold drawing, it is subjected to solid solution heat treatment with a solid solution heat treatment system of 560°C and a solid solution holding time of 70 minutes. After solid solution, it is immediately immersed in water cooling to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0141] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first stage aging temperature was 145°C, and the temperature was kept for 20 h; the second stage aging temperature was 185°C, and the temperature was kept for 36 h; and the extruded material was air-cooled to room temperature to obtain the corresponding aluminum alloy extruded material; the performance test results of the obtained aluminum alloy extruded bars are shown in Table 1.

[0142] Example 8

[0143] An aluminum alloy extruded bar, wherein the proportions of its component elements are as follows: by weight percentage, Mg 1.0%, Si 0.5%, Cu 0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.04%, B 0.02%, Ce0.04%, single impurity ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0144] The weight ratio of Mg element and Si element is controlled to be Mg / Si at 2; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot.

[0145] The ingot was heated from room temperature to 420°C and kept at this temperature for 10 hours, and then heated to 520°C and kept at this temperature for 6 hours to obtain an extruded ingot after homogenization heat treatment.

[0146] The extrusion process is as follows: the extrusion billet after homogenization heat treatment is extruded, and the extrusion process is as follows: the extrusion billet after homogenization heat treatment is heated to 530°C and kept warm for 0.5h. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 3m / min, and the extrusion ratio is 30.

[0147] After extrusion, the extruded material is cold drawn with a cold drawing amount of 5%. After cold drawing, it is subjected to solid solution heat treatment with a solid solution heat treatment system of 560°C and a solid solution holding time of 70 minutes. After solid solution, it is immediately immersed in water cooling to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0148] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first stage aging temperature was 145°C, and the temperature was kept for 20 h; the second stage aging temperature was 185°C, and the temperature was kept for 36 h; and the extruded material was air-cooled to room temperature to obtain the corresponding aluminum alloy extruded material; the performance test results of the obtained aluminum alloy extruded bars are shown in Table 1.

[0149] Example 9

[0150] An aluminum alloy extruded bar, wherein the proportions of its component elements are as follows: by weight percentage, Mg 1.0%, Si 0.5%, Cu 0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.04%, B 0.02%, Ce0.04%, single impurity ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0151] The weight ratio of Mg element and Si element is controlled to be Mg / Si at 2; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot.

[0152] The ingot was heated from room temperature to 420°C and kept at this temperature for 10 hours, and then heated to 520°C and kept at this temperature for 6 hours to obtain an extruded ingot after homogenization heat treatment.

[0153] The extrusion process is as follows: the extrusion billet after homogenization heat treatment is extruded, and the extrusion process is as follows: the extrusion billet after homogenization heat treatment is heated to 530°C and kept warm for 0.5h. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 3m / min, and the extrusion ratio is 30.

[0154] After extrusion, the extruded material is cold drawn with a cold drawing amount of 5%. After cold drawing, it is subjected to solution heat treatment with a solution heat treatment system of 520°C and a solution heat preservation time of 90 minutes. After solution, it is immediately immersed in water cooling to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0155] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first stage aging temperature was 145°C, and the temperature was kept for 20 h; the second stage aging temperature was 185°C, and the temperature was kept for 36 h; and the extruded material was air-cooled to room temperature to obtain the corresponding aluminum alloy extruded material; the performance test results of the obtained aluminum alloy extruded bars are shown in Table 1.

[0156] Comparative Example 1

[0157] An aluminum alloy extruded bar material, wherein the proportions of its component elements are as follows: by weight percentage, Mg 0.9%, Si 0.3%, Cu 0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Ce 0.025%, individual impurities ≤0.05%, total impurities ≤0.15%, the remainder being Al, and the total is 100%.

[0158] The weight ratio of Mg to Si is controlled to be Mg / Si at 3; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot;

[0159] The ingot was heated from room temperature to 420°C and kept at this temperature for 10 hours, and then heated to 570°C and kept at this temperature for 32 hours to obtain an extruded ingot after homogenization heat treatment.

[0160] The extruded billet after homogenization heat treatment is extruded, and the extrusion process is as follows: the extruded billet after homogenization heat treatment is heated in sections, the head is heated to 510°C, the middle is heated to 495°C, the tail is heated to 495°C, and kept warm for 0.5h; the mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 2m / min, and the extrusion ratio is 15.

[0161] After extrusion, the extruded material is cold drawn with a cold drawing amount of 8%. After cold drawing, it is subjected to solution heat treatment with a solution temperature of 540°C and a solution holding time of 70 minutes. After solution, it is immediately immersed in water and cooled to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0162] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first aging temperature was 135°C, and the temperature was kept for 15 hours; the second aging temperature was 175°C, and the temperature was kept for 20 hours; and the extruded material was air-cooled to room temperature to obtain the corresponding aluminum alloy extruded material. The performance test results of the obtained extruded bar are shown in Table 1.

[0163] Comparative Example 2

[0164] An aluminum alloy extruded bar material, wherein the proportions of its component elements are as follows: by weight percentage, Mg 0.6%, Si 0.5%, Cu 0.1%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.025%, individual impurities ≤0.05%, total impurities ≤0.15%, the remainder being Al, and the total is 100%.

[0165] The weight ratio of Mg to Si is controlled to be 1.2. The raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, etc. are melted according to the element ratio and cast to obtain the required ingot.

[0166] The ingot was heated from room temperature to 400°C and kept at this temperature for 7 hours, and then heated to 560°C and kept at this temperature for 20 hours to obtain an extruded ingot after homogenization heat treatment.

[0167] The homogenized heat treated extrusion billet is extruded, and the extrusion process is as follows: the homogenized heat treated extrusion billet is heated to 530°C and kept warm for 0.5h. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 3m / min, and the extrusion ratio is 30.

[0168] After extrusion, the extruded material is directly subjected to solution heat treatment without cold drawing. The solution heat treatment system is: solution temperature 560℃, solution holding time 20min. After solution, it is immediately immersed in water cooling to room temperature. Then the extruded material is straightened, and the straightening amount is ≤2%.

[0169] The straightened extruded material was subjected to aging heat treatment. The aging heat treatment system was as follows: aging temperature 165°C, insulation for 2 hours, and air cooling to room temperature to obtain the corresponding aluminum alloy extruded material. The performance test results of the obtained extruded material are shown in Table 1.

[0170] Comparative Example 3

[0171] An aluminum alloy extruded bar material, wherein the proportions of its component elements are as follows: by weight percentage, Mg 0.9%, Si 0.6%, Cu 0.25%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, B 0.015%, individual impurities ≤0.05%, total impurities ≤0.15%, the remainder being Al, and the total is 100%.

[0172] The weight ratio of Mg to Si is controlled to be 1.5. The raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-B master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot;

[0173] The ingot was heated from room temperature to 380°C and kept at this temperature for 4 hours, and then heated to 550°C and kept at this temperature for 8 hours to obtain an extruded ingot after homogenization heat treatment.

[0174] The homogenized heat treated extrusion billet is extruded, and the extrusion process is as follows: the homogenized heat treated extrusion billet is heated in sections, the head is heated to 510°C, the middle is heated to 495°C, the tail is heated to 485°C, and the temperature is kept for 0.5h. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 4m / min, and the extrusion ratio is 20.

[0175] After extrusion, the extruded material is cold drawn with a cold drawing amount of 2%. After cold drawing, it is subjected to solid solution heat treatment with a solid solution heat treatment system of 550°C and a solid solution holding time of 40 minutes. After solid solution, it is immediately immersed in water cooling to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0176] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first aging temperature was 125°C, and the temperature was kept for 5 hours; the second aging temperature was 165°C, and the temperature was kept for 2 hours; and the extruded material was air-cooled to room temperature to obtain the corresponding aluminum alloy extruded material. The performance test results of the obtained extruded bar are shown in Table 1.

[0177] Comparative Example 4

[0178] An aluminum alloy extruded bar, wherein the proportions of its component elements are as follows: by weight percentage, Mg 1.0%, Si 0.5%, Cu 0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.04%, B 0.02%, Ce0.04%, single impurity ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0179] The weight ratio of Mg element and Si element is controlled to be Mg / Si at 2; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot.

[0180] The ingot was heated from room temperature to 350°C and kept at this temperature for 8 hours to obtain an extruded ingot after homogenization heat treatment.

[0181] The homogenized heat treated extrusion billet is extruded, and the extrusion process is as follows: the homogenized heat treated extrusion billet is heated in sections, the head is heated to 530°C, the middle is heated to 510°C, the tail is heated to 495°C, and the temperature is kept for 1 hour. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 4m / min, the extrusion ratio is 30, and the extrusion outlet temperature is 530°C.

[0182] After extrusion, the extruded material is cold drawn with a cold drawing amount of 20%. After cold drawing, it is subjected to solution heat treatment with a solution temperature of 560°C and a solution holding time of 70 minutes. After solution treatment, it is immediately immersed in water and cooled to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0183] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: the first stage aging temperature was 145°C, and the temperature was kept for 20 h; the second stage aging temperature was 185°C, and the temperature was kept for 36 h; and the extruded material was air-cooled to room temperature to obtain the corresponding aluminum alloy extruded material; the performance test results of the obtained aluminum alloy extruded bars are shown in Table 1.

[0184] Comparative Example 5

[0185] An aluminum alloy extruded bar, wherein the proportions of its component elements are as follows: by weight percentage, Mg 1.0%, Si 0.5%, Cu 0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.04%, B 0.02%, Ce0.04%, single impurity ≤0.05%, total impurities ≤0.15%, the remainder is Al, and the total is 100%.

[0186] The weight ratio of Mg element and Si element is controlled to be Mg / Si at 2; the raw materials Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Zn master alloy, Al-Ti master alloy, Al-Fe master alloy, Al-Er master alloy, Al-B master alloy, Al-Ce master alloy, etc. are melted according to the element ratio, and cast to obtain the required ingot.

[0187] The ingot was heated from room temperature to 420°C and kept at this temperature for 10 hours, and then heated to 570°C and kept at this temperature for 32 hours to obtain an extruded ingot after homogenization heat treatment.

[0188] The homogenized heat treated extrusion billet is extruded, and the extrusion process is as follows: the homogenized heat treated extrusion billet is heated in sections, the head is heated to 530°C, the middle is heated to 510°C, the tail is heated to 495°C, and the temperature is kept for 1 hour. The mold temperature is 430°C, the extrusion barrel temperature is 420°C, the extrusion speed is 4m / min, the extrusion ratio is 30, and the extrusion outlet temperature is 530°C.

[0189] After extrusion, the extruded material is cold drawn with a cold drawing amount of 20%. After cold drawing, it is subjected to solution heat treatment with a solution temperature of 560°C and a solution holding time of 70 minutes. After solution treatment, it is immediately immersed in water and cooled to room temperature. The extruded material is then straightened with a straightening amount of ≤2%.

[0190] The straightened extruded material was subjected to aging heat treatment, and the aging heat treatment system was as follows: heating temperature was 150°C, holding time was 40h, and air cooling was performed to room temperature to obtain the corresponding aluminum alloy extruded material; the performance test results of the obtained aluminum alloy extruded bars are shown in Table 1.

[0191] Table 1 Properties of the extruded materials obtained in Examples 1 to 9 and Comparative Examples 1 to 5

[0192]

[0193] It can be seen from the test results in Table 1 that Examples 1 to 9 of the present invention improve the yield strength of the aluminum alloy while further improving the electrical conductivity of the aluminum alloy by optimizing the weight ratio between the component elements of the aluminum alloy and adding a specific proportion of Cu element and a small amount of Ce, Er and B elements; the present invention adopts a homogenization heat treatment process with a specific heat treatment temperature and holding time in a two-step method and an aging heat treatment process with a specific temperature and holding time in a two-step method, and the improvement of the formula and the improvement of the process work synergistically and jointly promote the improvement of the yield strength and conductivity of the aluminum alloy bar, and the yield strength (above 350 MPa) and conductivity (above 50% IACS) of the prepared aluminum alloy extruded bar are improved.

[0194] On the basis of the above process, the present invention further adjusts the cold drawing amount or optimizes the component ratio or optimizes the three-stage hot extrusion process to promote the improvement of the yield strength and conductivity of the aluminum alloy bar, and the yield strength reaches 300~350MPa, and the conductivity reaches 50%~55%IACS.

[0195] Comparative Example 1 and Examples 1 to 9 of the present invention are different in formulation, in which Si is 0.3%, Mg / Si is 3, and Ce is the only trace element added; the yield strength of the aluminum alloy bar prepared using the formulation and process conditions can reach 322 MPa, but the conductivity is 48.3% IACS, which is significantly lower than the conductivity of the embodiments of the present invention; this shows that the present invention controls the weight ratio of Mg / Si and the proportion of Si, adds three trace elements of Ce, Er and B, and affects the synergistic effect of other component elements and processes, and can significantly improve the conductivity of the aluminum alloy bar, such as the conductivity can reach more than 50% IACS.

[0196] Comparative Example 2 is different from Examples 1 to 9 of the present invention in terms of formula, in which only Er is added as a trace element; in terms of process, the hot extrusion process only adopts a one-stage process, that is, when the aluminum alloy bar is heated and extruded, the hot pressing temperature of the head, middle and tail parts is the same, and after the hot extrusion process, the cold drawing process is not performed and the solid solution heat treatment is directly performed, and the aging heat treatment adopts only a one-stage process; the conductivity of the aluminum alloy bar prepared by using this formula and process conditions can reach 51.3% IACS, but its yield strength only reaches 275 MPa, which is significantly lower than the yield strength of the aluminum alloy of the present invention. It is explained that the present invention adds three trace elements of Ce, Er and B in the raw material formula, adopts a three-stage hot extrusion process with a specific temperature, a cold drawing process with a specific cold drawing amount, and a two-stage aging heat treatment process, which can significantly improve the mechanical strength of the aluminum alloy bar, such as the yield strength can reach more than 300 MPa.

[0197] Comparative Example 3 is different from Examples 1 to 9 of the present invention in terms of formulation, in that only B is added as a trace element; in terms of process, the cold drawing amount of the bar after the hot extrusion process is completed is only 2%; the yield strength of the aluminum alloy bar prepared using this formulation and process conditions is 286 MPa and the conductivity is 48.5% IACS, which are significantly lower than the yield strength and conductivity of the aluminum alloy of the present invention. This indicates that the present invention adds three trace elements, Ce, Er and B, to the raw material formulation, and controls the cold drawing amount to 8% to 20%, which can significantly improve the yield strength and conductivity of the aluminum alloy bar, such as a yield strength of more than 300 MPa and a conductivity of more than 50% IACS.

[0198] Comparative Example 4 is different from Examples 1 to 9 of the present invention in the homogenization heat treatment process. Only one-stage homogenization heat treatment is used, and the heating temperature and holding time are different. The yield strength and conductivity of the obtained aluminum alloy rod are significantly lower than those of the present invention.

[0199] Comparative Example 5 is different from Examples 1 to 9 of the present invention in the aging heat treatment process. Only one aging heat treatment process is used, and the heating temperature and the insulation time are different. The yield strength and the conductivity of the obtained aluminum alloy bar are significantly lower than those of the present invention.

[0200] The above description shows that the composition ratio and process of aluminum alloy rods have a significant impact on the material strength and conductivity; the present invention improves the electrical conductivity of the alloy while ensuring the mechanical properties by designing the formula of each element of the aluminum alloy, coordinating a reasonable heat treatment system and extrusion process.

[0201] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0202] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An aluminum alloy bar, characterized in that: The aluminum alloy bar comprises the following components in weight percentage: Mg 0.6%~1.0%, Si 0.5%~0.9%, Cu 0.1%~0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.01%~0.04%, B 0.01%~0.02%, Ce 0.01%~0.04%; single impurity ≤0.05%, total impurity ≤0.15%, the balance is Al, totaling 100%; The aluminum alloy bar has a yield strength of 300-350 MPa and a conductivity of 50%-55% IACS.

2. The aluminum alloy bar according to claim 1, characterized in that: The aluminum alloy bar comprises the following components in weight percentage: Mg 0.8%~1.0%, Si 0.5%~0.8%, Cu 0.2%~0.4%, Mn ≤0.05%, Zn ≤0.05%, Ti ≤0.05%, Fe ≤0.05%, Er 0.02%~0.04%, B 0.01%~0.02%, Ce 0.02%~0.04%; single impurity ≤0.05%, total impurity ≤0.15%, the balance is Al, totaling 100%.

3. The aluminum alloy bar according to claim 1 or 2, characterized in that: The weight ratio of the Mg to the Si satisfies the following condition: 1<Mg / Si≤2.

4. The method for preparing the aluminum alloy bar according to claim 1, characterized in that: The preparation method comprises the following steps: Step S1: blending the aluminum alloy rod according to the proportion of each component in the aluminum alloy rod, and smelting to obtain an aluminum alloy ingot; Step S2: performing homogenization heat treatment on the aluminum alloy ingot to obtain a homogenization heat treated ingot; wherein the homogenization heat treatment includes a first-stage homogenization heat treatment and a second-stage homogenization heat treatment in sequence; the conditions of the first-stage homogenization heat treatment include: a heat treatment temperature of 380°C to 420°C and a holding time of 4 to 10 hours; Step S3: hot extruding the homogenized heat treated ingot to obtain an extruded rod; Step S4: cold drawing the extruded rod to obtain a drawn rod; Step S5: performing solution heat treatment on the drawn rod to obtain a solution heat treated rod; Step S6: sequentially performing stretching straightening and aging heat treatment on the solution heat treated rod to obtain the aluminum alloy rod; wherein the aging heat treatment sequentially includes a first aging heat treatment and a second aging heat treatment; the conditions of the first aging heat treatment include: a heating temperature of 125°C to 145°C and a holding time of 10 to 20 hours; the conditions of the second aging heat treatment include: a heating temperature of 165°C to 185°C and a holding time of 4 to 36 hours.

5. The method for preparing the aluminum alloy bar according to claim 4, characterized in that: The conditions of the second stage homogenization heat treatment include: the heat treatment temperature is 550°C to 570°C, and the holding time is 8 to 32 hours.

6. The method for preparing the aluminum alloy bar according to claim 4 or 5, characterized in that: The cold drawing amount of the cold drawing is 8% to 20%; and / or the deformation amount of the stretching straightening is ≤2%.

7. The method for preparing the aluminum alloy bar according to claim 4 or 5, characterized in that: The hot extrusion process includes: the heating temperature of the head of the homogenized heat treated ingot is 510°C to 530°C, the heating temperature of the middle part is 495°C to 510°C, the heating temperature of the tail part is 480°C to 495°C, and the total insulation time is 30min to 1h.

8. The method for preparing the aluminum alloy bar according to claim 4 or 5, characterized in that: The hot extrusion process further includes: the heating temperature of the hot extrusion mold is 420°C to 440°C, and the heating temperature of the extrusion barrel in the mold is 410°C to 430°C; And / or, the extrusion speed of the hot extrusion is 3-4 m / min, and the extrusion ratio is 20-30.

9. The method for preparing an aluminum alloy bar according to claim 4 or 5, characterized in that: The conditions of the solution heat treatment include: the solution heating temperature is 540°C to 560°C, and the solution holding time is 40min to 70min; And / or, the aluminum alloy bar after the solution heat treatment is water quenched to 15° C. to 35° C., and then subjected to the stretching straightening and the aging heat treatment.

10. Use of the aluminum alloy bar according to any one of claims 1 to 3 or the aluminum alloy bar obtained by the preparation method according to any one of claims 4 to 9 in radar, electromagnetic rail or transportation.

Citation Information

Patent Citations

  • Aluminum alloy cast rod used for hub and preparation method of aluminum alloy cast rod

    CN105543591A

  • High-conductivity aluminum-silicon-magnesium alloy for new energy automobile charging pile and manufacturing method of high-conductivity aluminum-silicon-magnesium alloy

    CN116200630A